National Media Narratives on The Identity of the Local Community of Cirendeu Indigenous Village - Naufal, Rasyid; Arifin, Hadi Suprapto; Iwan Koswara (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
This research aims to analyze how the national media's narrative concerning Kampung Adat Cirendeu influences the identity of the local community. Kampung Adat Cirendeu, situated in Cimahi City, West Java, is a traditional village that strives to preserve its customs and local wisdom amidst the pressures of modernization. Utilizing a qualitative approach with a framing analysis method, this study reveals that the media plays a crucial role in shaping public perceptions of indigenous identities through its framing of news coverage. The findings indicate that the media significantly impacts how the identity of the Cirendeu community is perceived by selectively highlighting specific aspects of their lives, such as their customs, cultural practices, and the challenges they face. The presentation of news by the media often emphasizes certain elements while downplaying others, thereby influencing public understanding and attitudes towards the traditional village. This study underscores the importance of media narratives in the construction of cultural identity and suggests that further research could explore the implications of media representation on indigenous communities' social and cultural dynamics.